2021
DOI: 10.1038/s41598-021-88407-0
|View full text |Cite
|
Sign up to set email alerts
|

Compressions of magnetorheological fluids under instantaneous magnetic field and constant area

Abstract: Compressions of magnetorheological (MR) fluids have been carried out under instantaneous magnetic fields. The yield strength of the MR fluid in compressive mode has been derived by assuming that it was a transformed shear flow in Bi-visous model. The compressive stresses have experimentally studied under different magnetic fields, different initial gap distances and different compressive velocities. The nominal yield shear stresses of the compressed MR fluid under different influential factors have been calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A sketch of compressing MR fluid between two parallel plates is shown Figure 10. Because the surface morphology of MR particles is usually rough (Covey and Stanmore, 1981; Gartling and Phan-Thien, 1984; Wang et al, 2021b), it will provide the basic strong friction between particles. Zhang et al have proposed a semiempirical model and found that the proposed model is compatible with the traditional dipole model when d / R >> 2 ( R is the radius of the particle and d is the distance between two particles), namely, the particles are not closed (Zhang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A sketch of compressing MR fluid between two parallel plates is shown Figure 10. Because the surface morphology of MR particles is usually rough (Covey and Stanmore, 1981; Gartling and Phan-Thien, 1984; Wang et al, 2021b), it will provide the basic strong friction between particles. Zhang et al have proposed a semiempirical model and found that the proposed model is compatible with the traditional dipole model when d / R >> 2 ( R is the radius of the particle and d is the distance between two particles), namely, the particles are not closed (Zhang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…These spikes are highly ordered self-organized structures. Furthermore, it has been reported that a ferrofluid placed under a magnetic field for over 35 years has kept its liquid state with no sign of sedimentation, showing the particular pattern of spikes and meaningful stability (Figure b) …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that a ferrofluid placed under a magnetic field for over 35 years has kept its liquid state with no sign of sedimentation, showing the particular pattern of spikes and meaningful stability (Figure 1b). 14 Research in ferrofluid synthesis has considerably increased in the past 50 years. While a large number of research articles published in the early years might not be available online, there has been a large increase in publications in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They exhibit a low viscosity of Newtonian fluids in the absence of magnetic fields and a high viscosity and low fluidity of Bingham fluids under magnetic fields. Moreover, the transition response between their fluid- and solid-like states is quick, and this transition process is reversible [ 3 , 4 ]. Given these advantages, MRFs have been applied in many engineering fields, such as polishing [ 5 ], sealing [ 6 ], braking [ 7 ], vibration control [ 8 , 9 ], etc.…”
Section: Introductionmentioning
confidence: 99%